(untitled) (مجلة إحالات, 2026)
In the following article that is under the title of The Oriental Imaginary in the Work of Isaac Muñoz, our objective will be to take a tour of Muñoz’s work dedicated to the Arab world. My intention is not to delve into the literary analysis of Muñoz’s work but rather to underline Muñoz’s view of the East during the first decades of the 20th century, a time marked by the memorialist discourse of the Spanish colonial period on African territories. Isaac Muñoz had a vision of the East, different from his contemporaries, a romantic, admiring, poetic and comforting look at his spirit as a writer who suffered from the crisis at the end of the century.